2019
DOI: 10.14710/jnc.v8i4.25833
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS KANDUNGAN GIZI DAN AKTIVITAS ANTIOKSIDAN PADA YOGHURT DENGAN PENAMBAHAN NANAS MADU (Ananas Comosus Mer.) DAN EKSTRAK KAYU MANIS (Cinnamomum Burmanni)

Abstract: Latar belakang : Penelitian ini bertujuan untuk mengetahui kandungan gizi dan aktivitas antioksidan pada yoghurt dengan penambahan nanas madu dan ekstrak kayu manis. Metode : Penelitian eksperimental dengan sampel yoghurt dengan penambahan nanas madu (0%, 20%, 40% dan 60%)  dan ekstrak kayu manis (2% dan 4%). Protein dianalisis dengan metode Bradford, lemak dianalisis dengan metode soxhlet, kadar air dianalisis dengan metode oven, kadar abu dianalisis dengan metode Drying Ash, karbohidrat dianalisis dengan met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…The percentage of free radicals that foodstuffs' antioxidants were able to bind to by using the DPPH method's results for assessing antioxidant activity was 50% (IC50). Less food is required to absorb free radicals the higher antioxidant activity and antioxidant levels are [8].…”
Section: White Oyster Mushroom Extract (Pleurotus Ostreatus) Added To...mentioning
confidence: 99%
“…The percentage of free radicals that foodstuffs' antioxidants were able to bind to by using the DPPH method's results for assessing antioxidant activity was 50% (IC50). Less food is required to absorb free radicals the higher antioxidant activity and antioxidant levels are [8].…”
Section: White Oyster Mushroom Extract (Pleurotus Ostreatus) Added To...mentioning
confidence: 99%
“…The higher the ash content contained, the higher the content of minerals. In addition, the components in minerals are also influenced by several things, such as plant species, geographical conditions, physiology and the type of material used (Kusumawati et al, 2020). However, all the yogurt drink produced still meets the Indonesian National Standard (SNI) 01.2981-2009 for yogurt products maximum ash content limit was 1% (Destiana et al, 2021).…”
Section: Ash Contentmentioning
confidence: 99%
“…[16] report that the addition of WPC protein contributes to shaping the consistency of yogurt. Water in fermented products is needed by lactic acid bacteria in carrying out the fermentation process [17]. However, [18] reported that the higher the total solids, the higher the total lactic acid bacteria.…”
Section: Chemical Characteristics Of Yogurtmentioning
confidence: 99%